At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To find the next 4 terms of the sequence given [tex]\( a = 3 \)[/tex] and the recursive formula [tex]\( a_n = a_{n-1} - 2 \)[/tex], follow these steps:
### Step 1: Identify the first term
The first term of the sequence is given as:
[tex]\[ a_1 = 3 \][/tex]
### Step 2: Use the recursive formula to find the next terms
Using the formula [tex]\( a_n = a_{n-1} - 2 \)[/tex], we can generate the next terms:
- Second term:
[tex]\[ a_2 = a_1 - 2 \][/tex]
Substituting [tex]\( a_1 = 3 \)[/tex]:
[tex]\[ a_2 = 3 - 2 = 1 \][/tex]
- Third term:
[tex]\[ a_3 = a_2 - 2 \][/tex]
Substituting [tex]\( a_2 = 1 \)[/tex]:
[tex]\[ a_3 = 1 - 2 = -1 \][/tex]
- Fourth term:
[tex]\[ a_4 = a_3 - 2 \][/tex]
Substituting [tex]\( a_3 = -1 \)[/tex]:
[tex]\[ a_4 = -1 - 2 = -3 \][/tex]
- Fifth term:
[tex]\[ a_5 = a_4 - 2 \][/tex]
Substituting [tex]\( a_4 = -3 \)[/tex]:
[tex]\[ a_5 = -3 - 2 = -5 \][/tex]
### Step 3: List all the terms
Including the initial term and the next four terms we calculated, the sequence is:
[tex]\[ 3, 1, -1, -3, -5 \][/tex]
Thus, the next 4 terms of the sequence are:
[tex]\[ 1, -1, -3, -5 \][/tex]
### Step 1: Identify the first term
The first term of the sequence is given as:
[tex]\[ a_1 = 3 \][/tex]
### Step 2: Use the recursive formula to find the next terms
Using the formula [tex]\( a_n = a_{n-1} - 2 \)[/tex], we can generate the next terms:
- Second term:
[tex]\[ a_2 = a_1 - 2 \][/tex]
Substituting [tex]\( a_1 = 3 \)[/tex]:
[tex]\[ a_2 = 3 - 2 = 1 \][/tex]
- Third term:
[tex]\[ a_3 = a_2 - 2 \][/tex]
Substituting [tex]\( a_2 = 1 \)[/tex]:
[tex]\[ a_3 = 1 - 2 = -1 \][/tex]
- Fourth term:
[tex]\[ a_4 = a_3 - 2 \][/tex]
Substituting [tex]\( a_3 = -1 \)[/tex]:
[tex]\[ a_4 = -1 - 2 = -3 \][/tex]
- Fifth term:
[tex]\[ a_5 = a_4 - 2 \][/tex]
Substituting [tex]\( a_4 = -3 \)[/tex]:
[tex]\[ a_5 = -3 - 2 = -5 \][/tex]
### Step 3: List all the terms
Including the initial term and the next four terms we calculated, the sequence is:
[tex]\[ 3, 1, -1, -3, -5 \][/tex]
Thus, the next 4 terms of the sequence are:
[tex]\[ 1, -1, -3, -5 \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.